Tenure, experience, human capital and wages: A tractable equilibrium search model of wage dynamics - Jesper Bagger; François Fontaine; Fabien Postel-Vinay; Jean-Marc Robin (Centre for Microdata Methods and Practice (cemmap), 2014)
We develop and estimate an equilibrium job search model of worker careers, allowing for human capital accumulation, employer heterogeneity and individual-level shocks. Career wage growth is decomposed into the contributions of human capital and job search, within and between jobs. Human capital accumulation is largest for highly educated workers, and both human capital accumulation and job search contribute to the observed concavity of wage-experience profiles. The contribution from job search to wage growth, both within- and between-job, declines over the first ten years of a career - the 'job-shopping' phase of a working life - after which workers settle into high-quality jobs and use outside offers to generate gradual wage increases, thus reaping the benefits from competition between employers.
Keywords: J24; J31; J41; J62; 330; Job Search; Human Capital Accumulation; Within-Job Wage Growth; Between-Job Wage Growth; Individual Shocks; Structural Estimation; Matched Employer-Employee Data